Product warranty handbook - Blischke, Wallace R.; Murthy, D. N. Prabhakar (Marcel Dekker, 1996)
Covering product warranties, this work offers comprehensive examinations of fundamental concepts and furnishes detailed, immediately applicable results. It sets out to bridge the gap between theory and practice, and integrates the research of various disciplines that study warranty, illustrating all basic consumer warranty options.